REPRESENTATION IN LABOUR LAW OF NATURAL ON LEGAL STATUS (Journal of actual problems of jurisprudence, 2019)
As subjects of labor relations representatives of the parties belong only to the employeein addition to rights, you must have the appropriate rights and responsibilities, as the employee must be himselfrights that belong only to other persons. (conclusion of employment contract, performance of duties)etc.).In our opinion, the legal status of representatives of employers and employees is specialwork has a special character related to legal capacity.